Reading comprehension of graduate students in IELTS (Journal of Tikapur Multiple Campus, 2017)
International Language Testing System (IELTS) is a prominent examination for the most of the youths in the world to pursue their study in the country where English is spoken as a native language. It has become the part of their career. As IELTS format consists testing of four language skills; listening, speaking, reading and writing, the researcher carried out to find the reading proficiency of the students studying in Bachelors level in relation to the scoring system. The researcher also aimed at exploring the difficulties faced by the students while attempting reading text. The sample size of the study consisted of 30 students studying in Humanities, Education and   anagement of Tikapur Multiple Campus. The informants were selected using purposive non random sampling in a proportionate way. A questionnaire consisting of five set of reading text based on IELTS examination was used as a data collection tool. The data were analyzed and interpreted descriptively and statistically. The result of the data obtained revealed that the reading proficiency of the students in IELTS text is extremely limited. The average band is three which indicates that the informants are categorized under extremely limited user. They convey and understand only general meaning in very familiar situations. Frequent breakdowns in communication occur.